Preferencias hacia la marca y origen del ajo (Allium sativum L.) - Velarde-Mendívil, Alma Teresita; Camarena-Gómez, Dena María; Salgado-Beltrán, Lizbeth (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
Garlic is one of the best known and most widely consumed vegetables in the international field. Regarding its production, Asian countries are identified as the main producers at a global level. Mexico have a significant production of garlic, occupying the fourth place for its productive volume in Latin America and in some regions such as the municipality of Arizpe, Sonora has a productive vocation, contributing to the region's economy and family support. Hence, for a significant number of small producers, it is essential to remain competitive in the garlic market. As a positioning strategy, the creation of a regional brand emerges as a feasible alternative. That is why, and in order to know the preferences that consumers manifest towards Arizpe garlic, an experiment of choice was carried out, a methodology widely used in agri-food marketing studies, the NGene software was used for the analysis of data and in the Limdep software, a conditional logit model was estimated. The results show that the manufacturer's brand and regional origin exert a positive influence on consumers. It is noted that consumers would be willing to pay a premium if the products have the regional or national brand attribute. This information suggests the possibility that exists for small producers in the study region to position themselves in the market with a regional garlic brand.